2019
DOI: 10.1111/ppl.13030
|View full text |Cite
|
Sign up to set email alerts
|

Influence of drought stress on pistil physiology and reproductive success of twoGossypium hirsutumcultivars differing in drought tolerance

Abstract: The causes of reproductive failure under drought stress (DS) are poorly understood. We hypothesized that reproductive failure was related to drought-induced changes in pistil biochemistry. To address this hypothesis, a water deficit-induced experiment was conducted with two cotton cultivars (Dexiamian 1, drought tolerant; Yuzaomian 9110, drought sensitive). Results showed that DS decreased the photosynthesis of subtending leaf and downregulated sucrose transporter gene (GhSUT-1) expression in pistil for both c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Pollen viability is an effective indicator that measures a plant’s ability to develop into seed and fruit; drought stress decreased pollen viability of tomatoes and other crops according to our findings and previous studies (Hu et al ., 2020); nevertheless, this was promoted by our fungal treatments under stressed and nonstressed conditions. Similarly, Talaromyces omanensis enhanced the pollen viability of tomatoes under natural and drought-stress conditions (Halo et al ., 2020).…”
Section: Discussionsupporting
confidence: 88%
“…Pollen viability is an effective indicator that measures a plant’s ability to develop into seed and fruit; drought stress decreased pollen viability of tomatoes and other crops according to our findings and previous studies (Hu et al ., 2020); nevertheless, this was promoted by our fungal treatments under stressed and nonstressed conditions. Similarly, Talaromyces omanensis enhanced the pollen viability of tomatoes under natural and drought-stress conditions (Halo et al ., 2020).…”
Section: Discussionsupporting
confidence: 88%
“…The strongest Cu/ZnSOD expression in tobacco, assessed by SodCc promoter-β-glucuronidase fusion, was observed, among generative organs, in ovules, stigma and pollen grains (Van Camp et al 1997). In stigmas of stress-resistant cotton cultivar, SOD activity was higher, and the level of ROS was lower than in the sensitive one (Hu et al 2020). At high temperatures in pearl millet, SOD activity on stigma decreased, and the level of ROS increased (Djanaguiraman et al 2018).…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, under salt stress, the expression of antioxidant enzyme-related genes (encoding APX and POD) in Arabidopsis thaliana L. pistils decreased, leading to large amounts of ROS, which ultimately led to the ovule abortion (Sun et al, 2005). Our previous study has found that drought during flowering will cause a higher H 2 O 2 level in cotton pistils to damage ovule activities, decreasing the fertilization rate (Hu et al, 2020).…”
Section: Asa Can Effectively Eliminate Omentioning
confidence: 98%
“…Similarly, under salt stress, the expression of antioxidant enzyme‐related genes (encoding APX and POD) in Arabidopsis thaliana L. pistils decreased, leading to large amounts of ROS, which ultimately led to the ovule abortion (Sun et al., 2005). Our previous study has found that drought during flowering will cause a higher H 2 O 2 level in cotton pistils to damage ovule activities, decreasing the fertilization rate (Hu et al., 2020). Nevertheless, studies on the effects of drought during the development of cotton ovule on ovule cytological structure and physiological and biochemical metabolism, and its relationship with the ovule formation are still not explored.…”
Section: Introductionmentioning
confidence: 99%